Necessary endings eaudiobook The employees, businesses, and relationships that all of us have to give up in order to move forward. - Cloud, Henry (2011)
"If you're hesitant to pull the trigger when things obviously aren't working out, Henry Cloud's Necessary Endings may be the most important book you read all year." —Dave Ramsey, New York Times bestselling author of The Total Money Makeover "Cloud is a wise, experienced, and compassionate guide through [life's] turbulent passages." —Bob Buford, bestelling author of Halftime and Finishing Well; founder of the Leadership Network Henry Cloud, the bestselling author of Integrity and The One-Life Solution, offers this mindset-altering method for proactively correcting the bad and the broken in our businesses and our lives. Cloud challenges readers to achieve the personal and professional growth they both desire and deserve—and gives crucial insight on how to make those tough decisions that are standing in the way of a more successful business and, ultimately, a better life.